Provenance-Based Assurance Model for Delay Tolerant Network - Soni, K; Prabadevi, B (International Journal of Computer Sciences and Engineering, 2025)
Use of End to End connectivity in today’s network connectivity is not secure due to its delay and disconnection. This problem can be avoided by the Provenance-based Assurance model proposed in this paper. This model first assures that a node is trustworthy and to whom the data will be sent. It evaluate trust by the information added by the message carrier as indirect clue when message is forwarding. So the problem of disconnection and delay can reduce by this strategy. This model first splits the file into packets then these packets will be encrypted by using DES algorithm with the secret key which is given by sender. After this we will cluster the nodes and send the packets to receiver’s end. Receiver will receive the packets and decrypt it using the same secret key which sender use for encryption. After decrypting it, receiver will get the original file content. This proposed system ensures high level of security with low communicational cost and high performance.